The Relationship between Digital Marketing Adoption and SMEs’ Performances in the Furniture Manufacturing Sector in Johor, Malaysia - Lam, Wei Liu; Azizan, Anim Zalina (Research in Management of Technology and Business, 2025)
This study examines the relationship between the performance of small and medium-sized businesses (SMEs) in the furniture manufacturing industry in Johor, Malaysia, and their digital marketing adoption. The foundation of Malaysia’s economy is made up of SMEs, and the furniture sector makes a substantial export contribution. However, obstacles to their development and competitiveness include poor digital adoption, antiquated marketing techniques, and resource limitations. The study aims to analyze the SMEs’ performances, determine the extent of digital marketing adoption, and investigate the relationships between them. The study uses a quantitative methodology and surveys furniture manufacturing SME stakeholders to offer practical advice to entrepreneurs and policymakers on how to improve SMEs’ performances through successful digital marketing tactics, promoting innovation, and local economic development.